2003
DOI: 10.1111/j.1651-2227.2003.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric utilization of a general emergency department in a developing country

Abstract: Aim: Knowledge of the spectrum and frequencies of paediatric emergencies presenting to an emergency department (ED) of individual developing countries is vital in optimizing the quality of care delivered locally. Methods: A prospective 6 wk review of all paediatric (< 18y) attendees to an urban ED was done, with patient age, presenting complaints, diagnoses, time of arrival and disposition recorded. Results: Complete data were available on 1172 patients, with an age range of 4 d to 18 y (mean ± SD 6.9 ± 5.6 y)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
1
10
1
4
Order By: Relevance
“…That is, infants are those with higher demand for the HEM emergency department, confirming data from several studies that assessed the utilization the different health care services (primary, secondary, and tertiary) by preschool children, especially from 0 to 2 years old (18)(19)(20)(21) . According to the collected data, it was found that most patients assisted by the HEM during the study period came from high densely-populated neighborhoods.…”
Section: Discussionsupporting
confidence: 67%
“…That is, infants are those with higher demand for the HEM emergency department, confirming data from several studies that assessed the utilization the different health care services (primary, secondary, and tertiary) by preschool children, especially from 0 to 2 years old (18)(19)(20)(21) . According to the collected data, it was found that most patients assisted by the HEM during the study period came from high densely-populated neighborhoods.…”
Section: Discussionsupporting
confidence: 67%
“…These personal traits may contribute to the perceived urgency of their illness, and hence their preference to use ED for their NE problems. Other researchers found that ED visits by children were for common pediatric illnesses [30,32] and non-traumatic injuries suggesting the use of EDs for primary care [33][34][35]. Parental anxiety may have also been a deciding factor especially after office hours [30].…”
Section: Discussionmentioning
confidence: 96%
“…El espectro de motivos de consulta descrito para cada rango etario y el bajo perfil de riesgo de los pacientes pediátricos en la admisión al SU son concordantes con los datos reportados en la literatura nacional e internacional 5,14,[17][18][19][20][21] . Sin embargo, las consultas por lesiones traumáticas e intoxicaciones fueron menos frecuentes en nuestro estudio (4,4% y 0,2%, respectivamente) comparado con otros estudios internacionales (20 a 40%) 5,19,20,22 , aunque similar a lo descrito en una cohorte de pacientes pediátricos atendidos en el Hospital Roberto del Río 14 .…”
Section: Discussionunclassified
“…Sin embargo, las consultas por lesiones traumáticas e intoxicaciones fueron menos frecuentes en nuestro estudio (4,4% y 0,2%, respectivamente) comparado con otros estudios internacionales (20 a 40%) 5,19,20,22 , aunque similar a lo descrito en una cohorte de pacientes pediátricos atendidos en el Hospital Roberto del Río 14 . Esta diferencia podría estar determinada en parte por el hecho de que nuestra institución no es un centro de referencia de trauma y haber excluido del análisis a los pacientes atendidos en el SU de traumatología.…”
Section: Discussionunclassified
See 1 more Smart Citation